Sedimentation-driven one-step fabrication of bifunctional single-layered triboelectric nanogenerator from sol-state composite precursor - Yoonsang Ra; Dongik Kam; Sunmin Jang; Sumin Cho; Donghan Lee; Dongwhi Choi (Friction)
Although the triboelectric nanogenerator (TENG) has been highlighted as a promising mechanical energy harvester, the requirement of stacking the two individual layers, contact and conductive layers, has been ball and chain around the ankle of unleashing potential and an advantage of TENGs in their application expansion and commercialization. Herein, one-step fabrication of a single-layered bifunctional composite film-based TENG (BF-TENG) driven by the sedimentation of a sol-state precursor is proposed for the extremely facile conversion of various ordinary items into energy harvesters. The BF-TENG consists of the polydimethylsiloxane (PDMS) matrix and a carbon nanopowder filler, and it includes both the dielectric part (DP) and conductive part (CP) in one single layer. The electrical percolation threshold of the incorporated concentration of carbon, ICC, for CP to act as a passage through which induced charges move in BF-TENGs is determined to be 1.0 wt%. The degree of carbon sedimentation in developing the proposed composite can be controlled by the curing speed and the probability of a crosslinking reaction. The maximum peak power is approximately 0.093 μW when the contact surface area is 78.5 mm2; the contact frequency is 8 Hz, and the connected load resistance is 9 MΩ. Based on these results, the electrical performance of BF-TENGs in response to various physical stimuli is characterized considering the mechanical energy sources available in daily life. Then, converting ordinary surfaces such as desks and human skin into BF-TENGs through a single coating procedure and harvesting energy to power an electric device are demonstrated as a proof-of-concept.